Mouthguard types, properties and influence on performance in sport activities: a narrative review - Wang, Ke; Liu, Yitong; Zhao, Zihe; Zhou, Shengjie; Zhang, Min (Frontiers in Medicine, 2025)
Mouthguards are proven devices placed inside the mouth to prevent oral lacerations, dental injuries, and jaw fractures. Endorsed by the World Dental Federation, mouthguards are crucial for preventing orofacial and dental trauma. However, their adoption in sports is challenged by limited guidance, communication barriers, and cost considerations. Based on extensive literature research in PubMed/MEDLINE, this narrative review summarizes the historical development of mouthguards, elaborates on their primary classifications, and examines the factors influencing their properties. Importantly, the impact of mouthguards on sports performance is clarified in this study. Overall, using mouthguards in sports not only reduces the occurrence and severity of dental injuries but also holds promise for enhancing athletic performances such as strength, aerobic capacity, agility, balance, and flexibility. Therefore, promoting mouthguard use in the sports community should be encouraged.